A study on impact of dairy farming vocational trainings on adoption of dairy entrepreneurship in south-western districts of Punjab - Bharat Singh Bhattu; Satbir Singh; Ajitpal Singh Dhaliwal; Mandeep Singh (Journal of Livestock Biodiversity, 2025)
Total 866 dairy farmers who have successfully completed dairy farming vocational training programmes from KVK, Bathinda, Mansa and Sangrur during the year 2011, 2012 and 2013 were selected for the collection of data. The information filled in a questionnaire from the trained farmers by visiting and discussing with them personally was analyzed for their adoption percentage to dairy entrepreneurship. The farmers were categorized in seven categories i.e. domestic (1-2 animals), marginal (3-5 animals), small (5-10 animals), medium (10-20 animals), large (20-100 animals), commercial (above 100 animals) and others who have not adopted this entrepreneurship. This study reveals 24.71% farmers this vocation as domestic, 16.85% as marginal, 11.54% as small, 07.04% as medium, 04.15% as large, and 01.96% as commercial while 16.97% were adopted dairy farming. It is also concluded that dairy training plays a significant role in bringing improvement in the socio-economic status of the farmers.